Anxiety and Stress among Dental Patients During the COVID-19 Pandemic - Prof Venkat Ramana Reddy Baddam; Prof Vikram Simha Bommireddy; Assistant professor Sanjana Marpuri; Prof Vikram Simha Bommireddy (International Dental Journal, 2023)
Aim or Purpose: COVID-19 pandemic posed a significant burden to several countries across the globe on the health, social, and economic fronts. There has been a transformation in people's behavior during the pandemic in light of the fear of infection and the uncertainty associated with the disease. The aim of this study was to ascertain the anxiety and stress among dental patients during the COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted among 1421 patients attending the outpatient department of a tertiary dental institution in the state of Andhra Pradesh. A self-administered questionnaire was used for data collection which was made available in both English and Telugu. Descriptive statistics and chi square tests were done to analyze the study data. Results: Subjects with no previous history of COVID-19 infection were found to be more anxious and stressful about COVID-19 compared to their counterparts. Fear of making family members vulnerable and the uncertainty of the prognosis in case of COVID-19 were the major reasons for anxiety and stress. The study subjects believed that seeking dental care during the pandemic is a risk factor for acquiring COVID-19. Most of the study subjects sought emergency care. Conclusions: The oral health fraternity needs to advertise the precautions being taken to curtail the possibility of transmission of infection in dental settings. Also, there is a necessity that the profession introspects the basic requirements of setting up an oral health care facility, especially by integrating the lessons learnt in the pandemic.